2005
DOI: 10.1098/rspb.2005.3261
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic microbial ancient DNA: a problem or an opportunity?

Abstract: Donoghue et al. 2004; Drancourt & Raoult 2005) that throw light on the evolution and spread of microbial pathogens in the past. In conclusion, rather than ancient microbial DNA being a problem (Willerslev & Cooper 2005), we agree with Pääbo et al. (2004) that this field, in particular that of pathogenic microbial ancient DNA, is potentially very exciting, and is already reaping results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 17 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The various responses to such criticisms (e.g. Donoghue and Spigelman, 2006) suggest that the differences in opinion stem at least in part from two underlying assumptions regarding the study of mycobacterial aDNA, assumptions which if correct would lessen the burden of authentication compared with, for example, equivalent research with human aDNA. We will examine these two assumptions in turn and then draw our own conclusions regarding the degree of rigor that is required in biomolecular studies of ancient TB.…”
Section: Biomolecular Evidence Must Be Rigorousmentioning
confidence: 95%
See 1 more Smart Citation
“…The various responses to such criticisms (e.g. Donoghue and Spigelman, 2006) suggest that the differences in opinion stem at least in part from two underlying assumptions regarding the study of mycobacterial aDNA, assumptions which if correct would lessen the burden of authentication compared with, for example, equivalent research with human aDNA. We will examine these two assumptions in turn and then draw our own conclusions regarding the degree of rigor that is required in biomolecular studies of ancient TB.…”
Section: Biomolecular Evidence Must Be Rigorousmentioning
confidence: 95%
“…Two reasons have been put forward for this enhanced preservation potential of mycobacterial DNA (Donoghue and Spigelman, 2006): the unique nature of the mycobacterial cell wall and the high guanine-cytosine (GC) content of mycobacterial DNA. We are not aware of any direct evidence that either of these factors can reduce the susceptibility of mycobacterial DNA to decay.…”
Section: Biomolecular Evidence Must Be Rigorousmentioning
confidence: 99%
“…Generally, it has been observed that the number of lineages increases in an exponential fashion across evolutionary time (Martin et al 2004). This distribution is greatly affected by the inclusion of only existing organisms in molecular phylogenies, as genetic information is available from extinct species only in vary rare and geologically recent circumstances (Gibbons 2005;Willerslev & Cooper 2005;Donoghue & Spigelman 2006). Applying a steady-state model of extinction and speciation, the deepest branches of a molecular phylogenetic tree cover, on average, half of the time the group is in existence (Zhaxybayeva & Gogarten 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When M. tuberculosis aDNA is being typed, there is little opportunity for contamination with modern genomic DNA, presuming (as was the case when we did this project) that modern M. tuberculosis DNA is not used as a positive control in the laboratories in which the work is carried out. This presumption has led some researchers to suggest that stringent anticontamination precautions are not necessary when ancient M. tuberculosis is being studied (51), but this view is erroneous (3). A major source of modern contamination in aDNA studies is No sequence reads None carryover of amplicons from previous PCRs in the form of aerosols generated when microfuge tubes are opened.…”
Section: Discussionmentioning
confidence: 99%